Sensory processing patterns and sleep quality in primary school children - Rajaei, Samira; Kalantari, Minoo; Pashazadeh azari, Zahra; Tabatabaee, Seyed Mehdi; Dunn, Winnie (Iranian Journal of Child Neurology, 2020)
ABSTRACT Objectives: Sensory processing and sleep quality affect children's academic performance and their quality of life. The purpose of this study was to investigate the relationship between sensory processing patterns and sleep quality in primary schoolchildren. Materials & Methods: In this cross-sectional study, 231 primary school students aged 7 to 12 years old (133 girls and 98 boys, mean age of 8.68±1.51) who were studying in schools in Tehran were randomly selected through cluster sampling. Researchers distributed a questionnaire for children's sleep habits to assess the quality of sleep and a Sensory Profile Questionnaire to assess the sensory processing patterns. Results: In this study, we found a meaningful moderate relationship between sensory processing patterns and the general scores of sleep habits (p <0.001) and each of the patterns of sensory processing (avoidance, sensitivity, seeking, and registration) had a negative relationship with areas of sleep habits (p =.005). Also, there was a significant difference between children who had more challenges with sleep and children with normal sleep patterns in sensory processing; mean differences in all four sensory quadrants were significant (p <001). Conclusion: Sensory processing patterns and sleep habits in primary school children have moderate correlation. Occupational therapists should consider the relationship between sensory challenges and sleep habits during their practice decisions with sensory challenges and sleep problems. Better sleep may occur with attention to sensory needs within the sleep routines. When sleep is better, this may lead to improved quality of life for the family and student performance at school.